Symptoms, SARS-CoV-2 Antibodies, and Neutralization Capacity in a Cross Sectional-Population of German Children - Laub, Otto; Leipold, Georg; Toncheva, Antoaneta A.; Peterhoff, David; Einhauser, Sebastian; Neckermann, Patrick; Borchers, Natascha; Santos-Valente, Elisangela; Kheiroddin, Parastoo; Buntrock-Döpke, Heike; Laub, Sarah; Schöberl, Patricia; et al. (Frontiers in Pediatrics, 2021)
Background: Children and youth are affected rather mildly in the acute phase of COVID-19 and thus, COVID19 infection may easily be overlooked. In the light of current discussions on the vaccinations of children it seems necessary to better identify children who are immune against SARS-CoV-2 due to a previous infection and to better understand COVID-19 related immune reactions in children. Methods: In a cross-sectional design, children aged 1-17 were recruited through primary care pediatricians for the study (a) randomly, if they had an appointment for a regular health check-up or (b) if parents and children volunteered and actively wanted to participate in the study. Symptoms were recorded and two antibody tests were performed in parallel directed against S (in house test) and N (Roche Elecsys) viral proteins. In children with antibody response in either test, neutralization activity was determined. Results: We identified antibodies against SARS-CoV-2 in 162 of 2832 eligible children (5.7%) between end of May and end of July 2020 in three, in part strongly affected regions of Bavaria in the first wave of the pandemic. Approximately 60% of antibody positive children (n=97) showed high levels (>97th percentile) of antibodies against N-protein, and for the S-protein, similar results were found. Sufficient neutralizing activity was detected for only 135 antibody positive children (86%), irrespective of age and sex. Initial COVID-19 symptoms were unspecific in children except for the loss of smell and taste and unrelated to antibody responses or neutralization capacity. Approximately 30% of PCR positive children did not show seroconversion in our small subsample in which PCR tests were performed. Conclusions: Symptoms of SARS-CoV-2 infections are unspecific in children and antibody responses show a dichotomous structure with strong responses in many and no detectable antibodies in PCR positive children and missing neutralization activity in a relevant proportion of the young population.